ACKNOWLEDGEMENTS. (18th December 2015) - Unknown
Abstract : Many institutions, colleagues, and friends have helped bring this volume together. The seeds began at the University of Wisconsin-Madison in 2009; they grew significantly during a stay at Durham University from 2012 to 2014; they bear fruit finally at the University of Nottingham now in 2015. I am grateful to all three universities for the opportunity to work on this project, grateful to the library staffs and interlibrary loan departments who consistently accepted and processed hundreds of my requests. I have been lucky to fall on my feet here in Nottingham, where new friends and colleagues have managed to make me feel at home in a matter of months, this despite consistently pointing out my unconscious Americanisms. The archives in which these documents are found deserve thanks not only for permission to publish but also for the courteous service I received while in situ . The British Library is justifiably a magnet for many early modernists, but Lambeth Palace Library has a wonderful charm all its own, the Huntington offers an idyllic setting in an otherwise busy environment, and the National Library of Scotland felt a home away from home for a time. For fellowship support during the research and writing, I am grateful to the University of Wisconsin-Madison's Department of History, the European Union's COFUND/Marie Curie Actions, and the Huntington Library.